Sistem Pakar Deteksi Minat Untuk Pemilihan Jenjang Karir Menggunakan Metode Certainty Factor - M. Tsana'uddin Farid; Hanung Adi Nugroho; Indriana Hidayah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Interests have an important role in the career path because interests will affect a person's performance, passion and abilities during their educational studies. The problem that occurs is that based on a survey conducted by the Indonesian Career Center Network, it was found that 87% of students in Indonesia felt that they were wrong in deciding which major they were taking. This problem is because the majors they take do not match their interests. This problem can be prevented by detecting interest early on so that career paths can be planned appropriately. This study aims to provide a solution to this problem by building an interest detection expert system to support career path selection. Certainty Factor methods are used in determining the output of the expert system to be built with the adaptation of the interest test tool, called RIASEC. Testing is done by comparing the system output results with expert consultation. The test results showed that the expert detection system was able to answer the interest with an accuracy of 93%. Based on the test results, the solution in interest detection expert system could be used as a reference assessment in planning career path choices